PAIN PERCEPTION OF OLDER ADULTS IN NURSING HOME AND HOME CARE SETTINGS: EVIDENCE FROM CHINA. (11th November 2018) - Jiang, N
Abstract: Objective: In the past decade, the number of long-term care (LTC) services for older adults in China has grown annually by an average of 10%. Older adults, their family members, and policy makers in China are concerned about patient outcomes in different care settings because older adults who have a similar functional status and LTC needs may choose either nursing home care or home care. The aim of this study was to compare pain perception in nursing home care and home care settings for physically dependent older adults in China. Methods: Multi-stage sampling method was used to recruit respondents aged 65 and older from Yichang City, China, in 2015. We employed a two-step analytical strategy – ordinary least square regression followed by propensity score matching method – to model the effect of contrasting residence types on pain perception. Results: Zero-inflated ordered probit regression analysis with participants unmatched (n = 484) showed that compared with older adults who received home care, those who received nursing home care did not have more severe pain (β=0.088, SE=0.196, p=0.655). After propensity-score matching, older adults in the home care group perceived less pain compared with the nursing home group (β=0.489, SE=0.169, p=0.004). Conclusion: The older adults who received home care perceived significantly less pain than the nursing home residents. The pain of older adults may differ based on the type of LTC services and therapy intensity they received, and home care might lead to less pain and better comfort than nursing home care.